Struktura aktu poznania teologicznego w ujęciu J. Ratzingera/Benedykta XVI - Szymik, Jerzy (Śląskie Studia Historyczno-Teologiczne, 2010)
The article raises a question of the process of origins underlying theological contents, that is, in other words, the individual stages of the theological cognition act. The basis of theology is philosophy, understood as a set of existential questions concerning happiness and immortality. God “touches” human hearts with His Grace, answering those questions, and this Grace is taken in faith. Whereas, theology is a “heart-seeking thought”, the heart having been moved by Divine revelation and faith itself. While developing throughout the space of thinking, theology looks for rational arguments for God’s answers given to existential questions. This is how theology gets to know reality and its epistemological acts are based on a source of the rationality of faith.